Terapi Bercerita Berpengaruh terhadap Kecemasan Akibat Hospitalisasi pada Anak Pra Sekolah - I Gede Yudiana Putra (Jurnal Gema Keperawatan, 2016)
The purpose of research to discover the effect of telling therapy against anxiety due hospitalization at pre school children in the pediatric ward. The research methodology using a pre-experimental research design, using one group pre-post test design againstone group without control. This research involved 38 respondentso pre school children in the pediatric ward. Result of research is Wilcoxon test results show that z is -5,477, and sig asymp (p-value) is 0,000. With such p-value 0,05, it;s mean there is a significant different in anxiety between before and after the child’s was given play therapy by telling. From the research can be conclusion there is the effect of play therapy of telling against anxiety due hospitalization at pre school children in the pediatric ward.